2009
DOI: 10.1007/s12265-009-9118-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of National Community Organization Cardiovascular Prevention Programs for High-Risk Women

Abstract: The purpose of this study was to reduce cardiovascular disease (CVD) risk in women by implementing a cardiovascular prevention health promotion program in faith-and community-based sites. The primary outcomes were reducing obesity and increasing physical activity. A longitudinal cohort of high-risk (age>40, ethnic minority) women (n=1,052) was enrolled at 32 sites across the USA. The pre-or post-educational intervention consisted of eight biweekly counseling sessions conducted over 4 months each addressing one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…A study on the outcome of a Know Your Numbers program on BP indicated that the knowledge for all health conditions assessed was closely associated with improved hypertension [10]. Outcomes of a cardiovascular prevention health promotion program targeting women indicated that increasing women's knowledge and awareness of heart disease increased their hypertension control and significantly reduced the mean BP in the entire cohort [11]. However, this may not be true for overall knowledge of hypertension in our study population.…”
Section: Discussionmentioning
confidence: 85%
“…A study on the outcome of a Know Your Numbers program on BP indicated that the knowledge for all health conditions assessed was closely associated with improved hypertension [10]. Outcomes of a cardiovascular prevention health promotion program targeting women indicated that increasing women's knowledge and awareness of heart disease increased their hypertension control and significantly reduced the mean BP in the entire cohort [11]. However, this may not be true for overall knowledge of hypertension in our study population.…”
Section: Discussionmentioning
confidence: 85%
“…However, we have previously published that similar educational programs sustained over a period of 4-6 months do, in fact, result in sustained improvements in heart disease risk profiles, a reduction in inflammatory burden, and cardiometabolic risk in racial/ethnic minority women. 6,20,42 In addition, others have demonstrated that awareness translates to action and poor health behaviors translate to physical health disorders, 44 pointing to the importance of awareness and knowledge as an important factor in the path to improved physical health. It is unclear as to what extent baseline knowledge predicted change in knowledge in our study, and whether the gains observed were, in part, attributable to lower baseline knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The survey questions are summarized in Table 1 and were provided to the study sites by the UC Davis Women's Cardiovascular Medicine Program to maintain uniformity for all sites. The instrument was available to women in English or Spanish, and it was adapted from one validated by the U.S. Department of Health and Human Services Office of Women's Health 6,20 and linked with the assessment of specific Healthy People 2020 heart disease outcomes (Heart Disease and Stroke objectives): http://www .healthypeople.gov/2020/topics-objectives/topic/heart-diseaseand-stroke/objectives Women were individually educated on the survey questions by a health professional at each of the five clinical sites …”
Section: Survey and Educational Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Similarly, a 7-month MI intervention resulted in no significant changes in physical activity among a large sample of African American women. 22 One identified study that used MI and SDT constructs to tailor health messages for diet and physical activity among African American adults showed no overall significant differences between treatment and control groups. 8 However, the SDT construct of autonomy support was shown to be a significant moderator of fruit and vegetable consumption and was also related to the correlations between autonomous and controlled motivation and fruit and vegetable intake.…”
Section: Sdt In Minority Populationsmentioning
confidence: 99%